Fault-tolerant control for four-wheel independent actuated electric vehicle using feedback linearization and cooperative game theory. (August 2020) - Zhang, Bohan; Lu, Shaobo
Abstract: This paper presents a novel fault-tolerant control (FTC) approach based on the cooperative game to guarantee the stability of four-wheel independent drive electric vehicles, in which four different players are modeled and interacted to find a solution to the FTC problem. First, a feedback linearization approach is employed to handle the nonlinearities in the system. Then, to study the interaction among actuators in an actuator failure scenario, the FTC problem can be viewed as a cooperative game so that its four players, namely the four in-wheel motors can cooperate to provide more stability of the vehicle. The distributed model predictive control theory is adopted as a general framework, the Pareto strategies among the players are derived using an interactive model based on a convex iterative method. Furthermore, the conditions that guarantee the practical stability of the closed-loop system are provided. The intrinsic differences between the cooperative game and noncooperative game are investigated via a numerical simulation. The effectiveness and real-time of the proposed control strategy are verified in a real-time hardware-in-the-loop test, and the results prove that the control strategy can effectively guarantee the stability of the vehicle in various actuator failure scenarios. Highlights: A fault-tolerant control scheme is designed for three types of actuator failure. The feedback linearization method is used to control the nonlinear MIMO system. The cooperative game theory is used to deal with the interaction among actuators. The potential of Pareto equilibrium in the cooperative game is theoretically explored. The performance of the control algorithm is verified by hardware-in-the-loop tests.